Childhood Physical Performance Measures and Adulthood Knee Cartilage Volume and Bone Area: A 25‐Year Cohort Study. Issue 9 (26th August 2015) - Antony, Benny; Jones, Graeme; Venn, Alison; Cicuttini, Flavia; March, Lyn; Blizzard, Leigh; Dwyer, Terence; Cross, Marita; Ding, Changhai
Abstract : Objective: We aimed to determine the associations between childhood physical performance measures and tibial cartilage volume and tibial bone area in adults 25 years later. Methods: Participants (n = 330, ages 31–41 years, female 47%) were selected from the Australian Schools Health and Fitness Survey of 1985. The participants underwent T1‐weighted fat‐suppressed magnetic resonance imaging (MRI) of their knees. Tibial bone area and cartilage volume were measured from MRI. Childhood measures, including physical work capacity at 170 beats per minute (PWC170 ), leg strength, number of sit‐ups, long‐run, and short‐run were measured in 1985. PWC170 and leg strength measures were repeated after 20 years in their adulthood. Linear regression analysis was used to determine the association of performance measures with cartilage volume. Results: There were consistent positive associations of all childhood measures, including PWC170 (β = 0.38 cm 2 per 10 watts, 95% confidence interval [95% CI] 0.15, 0.60), leg strength, long‐run, short‐run, and sit‐ups with adult medial and total tibial bone area. Similarly, there was an association of PWC170 and sit‐ups with adult medial tibial cartilage volume. After further adjustment for tibial bone area, the association between PWC170 and medial and total (β = 0.08 cm 3 per 10 watts, 95% CI 0.02, 0.10) tibial cartilage volume decreased in magnitude but remained significant. Conclusion: Childhood physical performance measures, especially PWC170, were associated with knee tibial bone area and cartilage volume in adulthood. The associations with cartilage volume appeared to be partially mediated by bone area. This suggests physical performance measures in childhood can independently influence adult knee structures.